Avaliação do potencial terapêutico da Bougainvillea glabra choisy frente à neurotoxicidade induzida por paraquat em Drosophila melanogaster - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The paraquat herbicide (PQ) is recognized as one of the main risk factors for the manifestation of Parkinson's disease (PD). PQ has already been shown to cause destruction of dopaminergic neurons, mitochondrial dysfunction and oxidative stress, being used as neurotoxin for the induction of PDlike symptoms in different experimental models. PD is characterized by motor alterations originating mainly from the selective and progressive loss of dopaminergic neurons. As oxidative stress plays an important role in the pathogenesis of PD, treatment with synthetic and / or natural antioxidants may be useful in slowing or preventing the onset of PD symptoms. Therefore, there is currently an intense search for natural antioxidants derived mainly from medicinal plants that may be effective in the treatment of PD symptoms. Extracts prepared from the leaves of Bougainvillea glabra are used in traditional medicine, however, their actions in the nervous system have not yet been studied. Thus, the objective of this work was to evaluate the possible neuroprotective effect of ethanol extract from B. glabra leaves (BG extract) on behavioral and biochemical changes in flies (Drosophila melanogaster) exposed to PQ. Wild type flies (male, 14 days old) were concomitantly exposed to a diet containing PQ (3.5 mM) and BG extract (120 μg /mL) for 4 days. After the treatment, behavioral and biochemical analyzes were performed. Flies exposed to PQ had a decrease in locomotor capacity and had a higher mortality than the control group. The neurotoxicity of PQ was also associated with a decrease in dopamine levels, increased activity of the acetylcholinesterase enzyme (AChE), and increased production of reactive species and lipid peroxidation. Coexposure with BG extract prevented mortality, improved locomotor performance, prevented depletion of dopamine levels, and decreased AChE activity, reactive species production and lipid peroxidation. The phytochemical analyzes of BG extract revealed the presence of important antioxidant compounds such as phytol, squalene, α, γtocopherol, stigmasterol, geranilgeraniol, quercetin and caffeic, vanillic, coumaric and ferulic acids. Our results show that B. glabra leaves can be considered an effective agent in the prevention of neurological disorders, where dopamine depletion and / or oxidative stress are involved in PD. Generally in pesticide toxicity studies with D. melanogaster, exposure to pesticides occurs by introducing them into the feed medium in agar medium. Unfortunately, this type of exposure has several limitations such as: uncertainty about the bioavailability and amount of pesticides ingested besides the high manipulation of the flies being treated due to the need of medium exchange. Thus, this work also aimed to develop a new method of exposure to pesticides in order to overcome the limitations of the method using the agar medium. We developed the method called "Continuous Liquid Feeding" (CLF). In this method, feed (along with the pesticide) is available in liquid form to the flies through suspended capillaries in the treatment vial. The CLF method presented several advantages over the agar method, such as: better feed bioavailability, lower reagent consumption, and little handling of the flies under treatment. We hope that the CLF method may be useful in future investigations on the toxicity of pesticides and that it can also be used in other areas that use D. melanogaster as an experimental model.
Therapeutic potential evaluation of Bougainvillea glabra choisy on paraquat induced-neurotoxicity in Drosophila melanogaster
Keywords: Paraquat; Oxidative stress; Neurotoxicity; Parkinson’s disease; Bougainvillea glabra; Drosophila melanogaster; Paraquat; Estresse oxidativo; Neurotoxicidade; Doença de Parkinson; Bougainvillea glabra; CNPQ::CIENCIAS BIOLOGICAS